O10.1 Tv in primary care: is there more out there than you think?. (13th September 2015) - Nicholls, J; Horner, P; North, P; Ferguson, R; May, M; Turner, K; Macleod, J; Muir, P
Abstract : Introduction: The Aptima TV NAAT test has recently been approved for use (sensitivity ~100%). Current microbiological testing involves wet mount microscopy (sensitivity 50%) or culture (sensitivity 75%). In practice, sensitivity rates may often be lower than this, due to deterioration of specimens during transport to the laboratory. Tests for Trichomonas vaginalis (TV) are often not performed on samples submitted from primary care because the prevalence is assumed to be too low for testing to be cost effective. The study objective was to determine the positivity of TV in women at risk of an STI, using Aptima TV NAAT in the following groups Symptomatic genitourinary medicine (GUM) Asymptomatic GUM Symptomatic primary care Asymptomatic primary care Methods: The Aptima TV NAAT test was performed on 9241 samples from women undergoing chlamydia and gonorrhoea NAAT testing in GUM and primary care. Results: The positivity of TV determined by TV NAAT was 4.8% (26/543) and 1.8% (28/1593) in women with and without symptoms attending GUM and 2.7% (95/3512) and 1.1% (41/3593) respectively in primary care. TV positivity rates were high, as expected, in those of black ethnicity attending GUM (15.5% in those with symptoms). However TV positivity rates in primary care varied by practice (0–5.8%) in a way that could not be attributed to ethnicity alone. Conclusion: This is the first study to report TV positivity, using a TV NAAT, in unselected women presenting for STI testing in primary care. Positivity proportions were higher than anticipated based on conventional testing methods particularly for symptomatic women in primary care. In view of the wide variation in TV positivity by locality, other factors e.g. deprivation may be important. This should be taken into consideration should targeted testing for TV be found to be cost effective, as targeting by ethnicity alone may miss cases. Disclosure of interest statement: Hologic provided the tests for the Aptima TV NAAT research study and have sponsored the authors to present this data at ISSTDR.